PENGARUH CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERASI - Hanivia Ramadhina (2021)
The purpose of this study was to determine the effect of corporate social responsibility disclosure and financial performance on firm value with institutional ownership as a moderating variable. The population in this research are non-financial companies listed on the IDX for the period 2017-2019. The number of samples are 111 samples. The method used in this research is quantitative method by analyzing panel data regression model, the classical assumption test, coefficient of determination, and partial test (t test). This study uses the STATA version 16 data processing program. The results from this research show that are corporate social responsibility disclosure does not have a significant effect on firm value. The financial performance variable has a significant positive effect on firm value. Meanwhile, institutional ownership as a moderating variable if it stands alone has a significant negative effect on firm value. However, for the interaction, institutional ownership cannot moderate or strengthen the relationship between CSR and financial performance to firm value.